Female Journalists in Mainstream Media in Facing The Challenges of Online Media in The Covid-19 Era - Wibawa, Darajat (Program Studi Ilmu Komunikasi, 2023)
For mainstream media, the outbreak of Covid-19 hit them hard as it complicates the existing challenges. The mainstream media have to deal with the Covid-19 effect, and at the same time must strive to survive online media attacks. This study aims to find out the relationship patterns, work processes, and effects of journalistic work among women journalists in mainstream media. This research uses a qualitative approach with a phenomenological strategy. Data was collected through in-depth interviews. Observations were also carried out to enrich the data. The results of this study can be constructed into three categories, namely relationship pattern, work process, and effect of journalistic work. This study conclude that patterns of relationships between mainstream media women journalists and their news sources are developed based on the principles of professionalism, idealism, and neutrality. The work process of women journalists consists of finding, collecting, processing, and publishing activities. The effects of journalistic work created by mainstream media women journalists occur in the form of praise, complaints, insults, and intimidation from news sources or the public.